A deterministic key pre-distribution scheme for WSN using projective planes and their complements. (1st January 2014) - Mitra, Sarbari; Dutta, Ratna; Mukhopadhyay, Sourav
We present two deterministic key pre-distribution schemes, one using projective planes and the other using complementary design of projective plane. The nodes are arranged hierarchically through a structure of ( p 2 + p )-nary tree, where p is a prime power. Our schemes are incumbent to more efficient resilience compared to the existing schemes. Each node requires storing significantly less number of keys. Furthermore, any number of nodes can be intrinsically inserted in the system by attributing a very few keys to the recently introduced nodes only. More interestingly, such node insertions in our schemes are done without interfering the normal functioning of the existing organised network.